Protocol to study toxic, immune, and suicidal phenotypes of killer yeast - Rianne C. Prins; Sonja Billerbeck (STAR Protocols)
Summary: Killer yeast produce antimicrobial proteins, often together with a self-protective immunity factor. Here, we present a protocol for analyzing the toxic, immune, and suicidal phenotypes in Saccharomyces cerevisiae. We describe steps for assessing toxicity via halo assays, suicidality through spot assays, and immunity using microtiter plate growth assays. We detail procedures for yeast culturing, performing the assays, and data analysis.For complete details on the use and execution of this protocol, please refer to Prins et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.